PEDAGOGICAL TRANSLATION IN ENGLISH TEACHING USED BY TEACHERS IN TEACHER EDUCATION PROGRAM - Muhammad . Guntar; Dina . Sartika; Rina . Mulya; Rizky Femilya Elsa (LINGUISTIK TERAPAN, 2022)
The purposes of this research were to analyze what situations teachers use translation (from English into Bahasa Indonesia and vice versa) in the Teacher Education Program classes and to describe how the teachers implement the translation in classroom. The research utilized descriptive qualitative method. The participants of the research were two English teachers in high school level in Jambi Province. The data were collected in the form of video recording and then the utterances were transcribed and analyzed based on the theory of situation of using translation proposed by Atkinson (1987), which consists of six situations namely: Eliciting Language, Checking Comprehension, Giving Instruction, Presentation, Checking for Sense, and Language Testing/Language Assessment. The result showed that there were five situations of using translation occurred in this study, they are eliciting language, checking comprehension, giving instruction, presentation and language testing/assessment. Further, pedagogical translation is very useful to facilitate the communication process in the classrooms by interpreting the information received in one language (L1) into another language (FL) and vice versa.